THE ROLE OF AGRICULTURAL EXTENSION WORKERS IN THE DEVELOPMENT OF FARMER GROUPS IN OFALANGGA VILLAGE, PANTAI BARU SUB-DISTRICT, ROTE NDAO REGENCY - Lusi, Asry Yanti; Pellokila, Marthen Robinson; Nainiti, Selfius P.N. (Buletin Ilmiah Impas, 2025)
Ofalangga Village, located in Pantai Baru District, Rote Ndao Regency, is one of the villages with significant agricultural potential in the local economy. The crops cultivated by the villagers of Ofalangga are rice, chili, and shallots. However, there are several problems often encountered by farmer groups in this village, such as a lack of government-provided facilities and infrastructure, as well as other obstacles like pests and diseases that damage farmers' crops. Therefore, this study aims to (1) determine the role of agricultural extension workers in the development of farmer groups in Ofalangga Village, Pantai Baru District, Rote Ndao Regency, and (2) identify the challenges faced by agricultural extension workers in the field in their efforts to develop farmer groups in Ofalangga Village, Pantai Baru District, Rote Ndao Regency. Research findings indicate that the role of agricultural extension workers in developing farmer groups in Ofalangga Village, Pantai Baru District, Rote Ndao Regency, is categorized as "Good" with a maximum score achievement percentage of 84.05%. The challenges faced by agricultural extension workers in their efforts to develop farmer groups in Ofalangga Village, Pantai Baru District, Rote Ndao Regency are: 1) Insufficient number of extension workers; 2) Inadequate facilities and infrastructure to support extension activities; and 3) Low participation of farmer group members.